Koralni preludiji Johanna Pachelbla - Miklavc, Polona (Muzikološki zbornik, 2011)
Johann Pachelbel wrote an extensive oeuvre of organ chorale preludes, the study of which opens historiographical as well as compositional and aesthetic questions. The article tries to present and compare the findings of various scholars about these questions, and to expose those issues that have remained unexplored and require further studies.
Keywords: 17.st.; 17th century; chorale preludes; German organ music; koralni preludiji; nemška orgelska glasba; Pachelbel, Johann, 1653-1706